A revision of the genus Radicipes Stearns, 1883 (Anthozoa: Octocorallia: Chrysogorgiidae) - Cordeiro, Ralf T. S.; Cairns, Stephen D.; Perez, Carlos D. (Zootaxa, 2017)
Radicipes is an octocoral genus composed of whip-like chrysogorgiids. Representatives of this group, also called ‘pigtails’, occur in almost all continental margins around the globe. Since its description in the 19th century, no comprehensive revision of this genus has been made. Thus, we present herein a revision of Radicipes, with descriptions of previously known species and one new species, Radicipes stonei. Type specimens from several museums were examined and seven species are considered valid. A distribution map of the genus and illustrations for all species are provided and a brief discussion is given on the possibility of additional undescribed species.